Procedural Pain Management in Patients with Cerebral Palsy Undergoing Botulinum Toxin Injection: A Systematic Review and Meta-Analysis - Silvia Faccioli; Alessandro Ehsani; Shaniko Kaleci; Giulia Tonini; Ilaria Tagliani; Mario Vetrano; Silvia Sassi (Toxins, 2025)
Background: The aim of this systematic review is to investigate effectiveness and safety of sedation–analgesia techniques in controlling pain during botulinum injections in patients with cerebral palsy (CP). Methods: The Pubmed, Cinahl, and Scopus databases were searched. Inclusion criteria were as follows: cerebral palsy; any type of outcome measure regarding pain and side effects assessment; any type of studies; and English language. RoB2 and Robins-I were applied to assess the risk of bias. Tables and forest plots synthetized the findings. Results: Seventeen reports were included; most regarded pain control, and ten investigated side effects. Three were RCTs, three were controlled, and twelve were observational studies. Several techniques were used, often in combination, such as non-pharmacological approaches (clown care or virtual reality); topical anesthesia with Emla®®, vapocoolant spray, or ice; and light-to-deep sedation with inhaled nitrous oxide, intranasal fentanyl, rectal, enteral, or intravenous midazolam, or intravenous ketamine or propofol. Vomiting and oxygen desaturation were uncommon complications. Conversely, the pooled incidence of other minor side effects was 6.39% (95% CI: 1.47–14.42%) under the random-effects model, with considerable heterogeneity. Conclusions: All the techniques are safe, if administered in an appropriate setting. Deep sedation is more effective in pain control but requires an anesthetist. A combined individualized approach is preferrable. PROSPERO CRD42025639999.